Sportivnaja trenirovannost': Paradoksy diagnostiki - Volkov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The term "preparedness" is meant as the condition of an organism reached with the help of any training load which contents can be different on the influence and composition. The specificity of the display of training ability properties of an organism is the capability to change during performance of muscular, intellectual, emotional etc. loads. Despite of different character of perturbing factor the genesis is the same. The term "preparedness" is an equivalent to the concept "state of health" which is understood as "the condition of full physical, emotional, social well-being". The test of the immunologic resistance with the use of the one of the basic components of immune system - phagocytos with the parallel studying the metabolic activity by the method of cytochemistry was applied as an objective method of diagnostics of health in practice of sports. The phagocytos appeared the indicator not only in relation to other parts of immunity, but in diagnostics of the general condition of an organism also. The index of Right - an average of germs (Staphyliciccus anrens or E. Colli), phagocyted by one neutrophil and an index of the Hamburger - amount phagocyting neutrophils from 100 researched was calculated. The integrity of phagocytos and the metabolic activity allow to operate the formation of the preparedness condition, to influence the choice of the methods of sports training, to regulate and to optimize a training load.